1991
DOI: 10.1007/bf02842106
|View full text |Cite
|
Sign up to set email alerts
|

Multiphoton geometrical isomerization of ClFC=CFCl. Selective purification of thetrans isomer

Abstract: A selective purification of the trans isomer of CFCI=CFCI was accomplished by multiphoton induced isomerization. The effect of pressure and fluence on the isomerization yield was also investigated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1997
1997
1997
1997

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
(4 reference statements)
0
1
0
Order By: Relevance
“…Previous studies performed with a mixture of cis-and trans-ClFCdCFCl showed that the cis isomer could be selectively excited to yield trans-ClFCdCFCl with a low reaction probability (10 -2 ), even at relatively high energy fluences (5 J cm -2 ). 17 Since the present experiments were performed at a lower fluence (1 J cm -2 ) and with a mixture of both isomers diluted in Ar, the IRF lost profile could be considered free of any chemical process.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies performed with a mixture of cis-and trans-ClFCdCFCl showed that the cis isomer could be selectively excited to yield trans-ClFCdCFCl with a low reaction probability (10 -2 ), even at relatively high energy fluences (5 J cm -2 ). 17 Since the present experiments were performed at a lower fluence (1 J cm -2 ) and with a mixture of both isomers diluted in Ar, the IRF lost profile could be considered free of any chemical process.…”
Section: Resultsmentioning
confidence: 99%